Phytotoxicity and uptake of arsenic through Pennisetum purpureum in a pilot-scale constructed wetland arrangement - Rahman, Md Ekhlasur; Mahmud, Khairil; Uddin, Md Kamal; Shamsuzzaman, S. M.; Shukor, Mohd Yunus Abd; Ghani, Siti Salwa Abd; Akter, Amaily; Nabayi, Abba; Sadeq, Buraq Musa; Chompa, Sayma Serine; Halmi, Mohd Izuan Effendi Bin (Taylor and Francis Ltd., 2025)
Phytoremediation is an evolving green technology based on utilizing hyper-accumulator plant species that can tolerate and accumulate elevated amounts of arsenic present in the surroundings. The purpose of this research was to identify the toxicity symptom of As including how much amount of As that Pennisetum purpureum Schumach can uptake in a CW arrangement. In this experiment, phytotoxicity and As uptake through P. purpureum Schumach were assessed at numerous As levels of 5, 22, and 39 mg kg−1 in CWs. The total extractable arsenic and bioavailable arsenic levels was determined using the wet digestion and the Na2-EDTA process correspondingly and both the As was assessed through ICP-OES. Results showed the symptoms of phytotoxicity at all As concentrations after 42 days of exposure, as the ratios of plant numbers to total mass of As were 0.0103, 0.0023, and 0.0013, which were very low. Arsenic-caused phytotoxicity symptoms enhanced with increasing arsenic concentrations in the spiked sand and periods of treatment indicating that As can be hazardous to P. purpureum Schumach when absorbed and accumulated in its cells. The density of the available As in the treated sand was reduced, including eliminated 100%, 91.5%, and 82.5% for 5, 22, and 39 mg kg−1As on 42 days separately. Highest As uptake by the whole P. purpureum Schumach plants reached 5733 ± 68.8 mg kg−1 DW on 42 days at 39 mg kg−1As level. These findings recommend that Pennisetum purpureum Schumach can be utilized for arsenic phytoremediation in agriculturally contaminated areas and anthropogenically contaminated ecosystems owing to its maximum capacity to uptake and accumulate arsenic.